Saring sebelum Sharing, Menangkal Berita Hoax, Radikalisme di Media Sosial - Sabiruddin Sabiruddin (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This article reports on concerns about hoax news, radicalism has spread on social media (social media). This concern surfaced when the hoax spread to boil down to utterances of hatred. This article aims to find out hoaxes on social media then look for solutions. The research method used is framing analysis conducted by gathering all the contents of the news about hoaxes and radicalism. This study analyzes and concludes eight news themes about: 1) Term of social media and radicalism. 2) The use of social media in spreading radical viruses. 3) Highlight social media irregularities. 4) Hoax War, encourage online media verification. 5) Social media and environmental health. 6) Our hoaxes and Indonesianness. 7) Dispelling hoax outbreaks, 8) Hoax outbreaks; false news on social media.